The best Christmas pageant ever [videorecording (DVD)] - Swanson, Ryan (Screenwriter); Clark, Platte F.; McDaniel, Darin; Greer, Judy, 1975-; Holmes, Pete, 1979-; Wright, Molly Belle; Schneider, Beatrice; Billingsley-Rodriguez, Sebastian; Lamb, Matthew (Actor); Moore, Essek; Woller, Kirk B. R., 1962-; Wood, Ewan Matthys; et al. (Lionsgate, 2025)
The Herdmans are absolutely the worst kids in the history of the world. They lie, they steal, they bully ... and now they've hijacked the town Christmas pageant. It follows six siblings who sneak into church searching for snacks and walk away with the lead roles in the town pageant. Grace is directing the performance for the very first time, but she and her daughter Beth and husband Bob are in over their heads, especially against a town that wants them to kick the Herdmans out. But the play's mischievous stars might unwittingly teach a community the true meaning of Christmas.